Bekumpang : Ritual Tolak Bala Suku Dayak Linoh Desa Solam Raya Kabupaten Sintang - noviana noviana; Arkanudin Arkanudin; Hasanah Hasanah (Universitas Tanjungpura, 2022)
Bekumpang is one of the Tolak bala traditions carried out by the Linoh Dayak ethnic community in Solam Raya Village when there is a disease outbreak that attacks. This study aims to describe the process and to explore the values of the ritual of the Kumpang. The method used in this research is ethnography observation, interviews and documentation as the primary data collection techniques. While the descriptive data analysis is used for the analysis phase. The purpose of the bekumpang ritual is to ask for protection from the Petara (God) so that all Solam Raya villagers are protected from epidemics of infectious diseases, both medically curable and incurable diseases. The factors behind the Linoh Dayak ethnic community carrying out the bekumpang ritual are the first because of the Covid-19 outbreak and the second because of public awareness of the importance of maintaining local wisdom. The ritual of Bempangpang contains aesthetic, religious, and social values.